Exploring the Visionary Leadership Model and Leadership Competencies in Developing an Islamic School - Isnada Waris Tasrim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study explores the visionary leadership model and leadership competencies in the development of Islamic schools. The research was conducted at the Manunggal Bangsa Education Foundation in Malang City, East Java, Indonesia, which manages educational institutions from kindergarten to senior high school. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and document analysis, and analyzed using an interactive model. Data trustworthiness was ensured through credibility, dependability, and confirmability, including triangulation of sources and methods and member checking. The findings reveal that the visionary leadership model practiced by the school founder and principal comprises a synergistic “Vision Process Triangle” with three stages: vision formulation, vision transformation, and vision implementation. Leadership competencies were found to be essential to the successful development of Islamic schools, particularly during the implementation phase. These competencies include principal–staff relations, student relations, community and parent engagement, organizational and facilities management, and curriculum and program development. The study recommends future research through comparative studies across Islamic educational foundations, longitudinal quantitative studies on leadership and student achievement, and experimental studies examining the effectiveness of visionary leadership training for school principals.